Thanatophoric skeletal dysplasia: a rare case report - Arora, Rishabh; Holla, Vijaya Narayana K. (International Journal of Research in Medical Sciences, 2024)
A diverse range of bone growth disorders known as skeletal dysplasias are brought on by new mutations in the FGFR3 gene, which cause abnormalities in the size and shape of the skeleton. We present a case of thanatophoric dysplasia diagnosed antenatally on ultrasound. G2P1L0, a 30-year-old woman, came to our radiodiagnosis department for her first pregnant ultrasound examination. The results showed a single live intrauterine baby with a head that was considerably bigger than the rest of the body, a hypoplastic nasal bone, an exceedingly thin fetal thorax, thicker soft tissue in the hands and feet, as well as bent long bones that resemble telephone receiver handles, along with bilateral club feet and trident hands.